2020
DOI: 10.1177/0972150920918468
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Impact of IFRS Convergence in India on Debt–Equity Components of Financial Statements

Abstract: The present article analyses the impact of International Financial Reporting Standards (IFRS) convergence on financial statements in India. Our focus is on the most significant and challenging standard, that is, IND-AS (financial instruments). Our focus is on the most significant and challenging standard i.e IND-AS(Financial Instruments) and their impact on debt-equity classification brought about by the new standard(s). We analyse the annual reports of 30 listed entities having outstanding preference share ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Mandatory preparation of financial reports as per IFRS is a very recent phenomenon in India. Hence, some base level studies, such as Kaaya (2015), Jain and Gupta (2020) and Tawiah and Boolaky (2020), found the differences between accounting figures as per IFRS and earlier accounting standards and their impact on accounting values. To repeat, from April 1 2016, India has implemented the new framework of accounting standards (Ind AS) that seeks to converge with IFRS and not fully adopt them.…”
Section: Ind As Affecting Indian Firmsmentioning
confidence: 99%
“…Mandatory preparation of financial reports as per IFRS is a very recent phenomenon in India. Hence, some base level studies, such as Kaaya (2015), Jain and Gupta (2020) and Tawiah and Boolaky (2020), found the differences between accounting figures as per IFRS and earlier accounting standards and their impact on accounting values. To repeat, from April 1 2016, India has implemented the new framework of accounting standards (Ind AS) that seeks to converge with IFRS and not fully adopt them.…”
Section: Ind As Affecting Indian Firmsmentioning
confidence: 99%
“…The adoption of new accounting standards, that is, Ind AS has significantly impacted the debt and equity components, valuation of assets, and other aspects of the firm's financial statements (Jain & Gupta, 2020). These changes are likely to affect the leverage and profitability contents of the firms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, under Ind AS, the treatment of leases, derivatives, preference shares, and convertible shares, differs from previous accounting standards. These changes can impact a firm's reported leverage ratios or interest coverage ratios (Jain & Gupta, 2020). Consequently, the relationship between leverage and firm performance may be influenced.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%